Response of Asias halodendri (Pallas) (Coleoptera: Cerambycidae) males and females to the odours of the different body parts of the opposite sex. (3rd April 2023) - Gao, Wenfang; Liu, Xinyu; Qin, Dongyu; Zhang, Tiantian; Ren, Rui; Wei, Dan; Xiao, Fangshu; Liu, Qiang; Zhu, Gengping; Pan, Lina; Li, Min
ABSTRACT: Asias halodendri (Pallas) is a polyphagous xylophage native to Asia and the biggest threat to Tetraena mongolica Maxim extinction. In this study, we attempted to locate the site of pheromone emission in A. halodendri . Different body parts, which included the wing, thorax, abdomen, and genital segments, of male and female A. halodendri were used in the olfactometry and electroantennographic experiments. Results showed that the male and female responses were stronger when the abdomen or abdominal extracts were applied as stimuli than when other body parts were used. Thus, the pheromone production system in A. halodendri is presumably located at the abdominal region.